O significado da implementação da reforma curricular no Colégio Militar de Fortaleza em direção à interdisciplinaridade e à visão de competência - Diorio, Renata Rovaris (2014)
The reconstruction of the curriculum of the Brazilian Military School System (SCMB) is a part of a huge Project that the Brazilian Army has chosen towards the modernization of its system, in a new context that it involves other demands from this millennium with the adoption of the pedagogical model of teaching by means of competences. This approuch enphasizes other methodologies and practices. This reseach has been motivated by the following questioning: how is the process of curricular changes at CMF which belongs to the SCMB happening? The main objective for this study is to analyze this process by the following categories: Curriculum, Interdisciplinarity and the pedagogical model of teaching by means of Competences. Other aims are added to them, such as: to describe the process of reconstruction of the curriculum at CMF, analyzing the officials documents from the curriculum, the DCNEM, the PCN and also the SCMB specific documents, among others, focusing on the following categories: curriculum, interdisciplinarity and the pedagogical model of teaching by means of competences; to analyze the given meanings of the target categories by the participants of this research; to caracterize the teacher’s way in this path of the curriculum reform based on the English Language Teaching (LEM) example. The methodological tool used for this researcch was the Content Analysis Technique. The collected data has showed us that we are in the process of migration towards the new concepts of teaching and learning processes. Moreover, they have also showed us that the way of teaching and learning English is an example of interdisciplinarity and multicultural scenario, therefore other practices have already taken place at CMF and they have showed us that the teachers’s concepts have been changed. The teachers have already found other ways to teach, so a new portrait has been built up with the interdisciplinarity, the contextualization of the contents and the multiculturalism ingredients. However, the relink of the different areas of the knowledge, the interaction and the integration of these fields have been done, there is still much work to do on this way.